Comparison of an HPTLC method with the Reflectoquant assay for rapid determination of 5-hydroxymethylfurfural in honey - Hošťálková, Anna; Klingelhöfer, Ines; Morlock, Gertrud E (Analytical and bioanalytical chemistry, 2013)
5-Hydroxymethylfurfural (HMF) was analyzed in 17 botanical varieties of honey from 12 countries. A recently developed high-performance thin-layer chromatographic (HPTLC) method was limited because of increased matrix effects at higher honey sample loading. Therefore, the method was modified to achieve higher sensitivity and eliminate matrix interference by use of rectangular application combined with a focusing step. The HPTLC results were compared with results from the new spectrophotometric Reflectoquant hydroxymethylfurfural assay. Both methods had quantification limits of 4 mg kg(-1) and were suitable for rapid quantification of HMF in honey at the strictest regulated level of 15 mg kg(-1). Comparable results were obtained for the 17 honey samples, with a mean deviation of 2.9 mg kg(-1) (15%). The optimized HPTLC method was proved to be highly matrix-robust and was validated for the 17 different honey matrices (correlation coefficients ≥0.9994 (n = 6), mean intra-day precision 3.2% (n = 3 within a plate; n = 2 repeated within a day), mean inter-day precision 3.7% (n = 3), mean reproducibility over the whole procedure including sample preparation 4.1% (n = 2), and mean recovery 106.9% (n = 5 different concentrations; n = 4 different honey matrices). Recovery for a range of different application volumes, and thus for different honey matrix loading, differed by only ≤4.2%. HMF results when calculated by use of external calibration and by use of the standard addition method varied by 8.8%. Both revealed that any matrix effect was minor and that the original matrix interference problem was successfully solved.
Keywords: Spectrophotometry; Reproducibility of Results; kontaminace potravin; chromatografie na tenké vrstvě; reprodukovatelnost výsledků; Chromatography, Thin Layer; 2-furaldehyd; med; spektrofotometrie; Furaldehyde; Honey; Food Contamination